2016
DOI: 10.18632/oncotarget.11110
|View full text |Cite
|
Sign up to set email alerts
|

Targeting antisense mitochondrial ncRNAs inhibits murine melanoma tumor growth and metastasis through reduction in survival and invasion factors

Abstract: We reported that knockdown of the antisense noncoding mitochondrial RNAs (ASncmtRNAs) induces apoptotic death of several human tumor cell lines, but not normal cells, suggesting this approach for selective therapy against different types of cancer. In order to translate these results to a preclinical scenario, we characterized the murine noncoding mitochondrial RNAs (ncmtRNAs) and performed in vivo knockdown in syngeneic murine melanoma models. Mouse ncmtRNAs display structures similar to the human counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(93 citation statements)
references
References 70 publications
18
75
0
Order By: Relevance
“…As reported previously by our group, knockdown of ASncmtRNAs with a specific ASO induces apoptotic death of tumor cells, while leaving normal cells unaffected, suggesting this strategy for the development of an efficient therapeutic approach for cancer (Borgna et al., ; Lobos‐Gonzalez et al., ; Vidaurre et al., ). We also reported that, in the syngeneic in vivo B16F10 murine melanoma model, an ASO directed to the mouse ASncmtRNAs delays tumor growth and considerably reduces metastasis, resulting in enhanced survival (Lobos‐Gonzalez et al., ). Up to date, there are two FDA‐approved ASOs, for treatment of cytomegalovirus retinitis (fomivirsen) and familial hypercholesterolemia (mipomersen) (Aartsma‐Rus, ; McGowan et al., ; Vitravene Study Group, , ), and there are currently many ongoing clinical trials involving ASOs for treatment of different pathologies, including cancer (clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As reported previously by our group, knockdown of ASncmtRNAs with a specific ASO induces apoptotic death of tumor cells, while leaving normal cells unaffected, suggesting this strategy for the development of an efficient therapeutic approach for cancer (Borgna et al., ; Lobos‐Gonzalez et al., ; Vidaurre et al., ). We also reported that, in the syngeneic in vivo B16F10 murine melanoma model, an ASO directed to the mouse ASncmtRNAs delays tumor growth and considerably reduces metastasis, resulting in enhanced survival (Lobos‐Gonzalez et al., ). Up to date, there are two FDA‐approved ASOs, for treatment of cytomegalovirus retinitis (fomivirsen) and familial hypercholesterolemia (mipomersen) (Aartsma‐Rus, ; McGowan et al., ; Vitravene Study Group, , ), and there are currently many ongoing clinical trials involving ASOs for treatment of different pathologies, including cancer (clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 73%
“…In addition, invasive properties of tumor cells are hindered by the in vitro treatment. At the molecular level, the observed effects on viability and invasiveness are mediated by a strong downregulation of survivin and factors associated with epithelial–mesenchymal transition, such as N‐cadherin and metallopeptidase‐9, among others (Borgna et al., ; Lobos‐Gonzalez et al., ; Vidaurre et al., ). These global effects on tumor cell viability and invasiveness exerted by ASK strongly suggest the potential of this approach for the development of an effective and safe therapeutic strategy against different types of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few 16S-rRNA-containing chimeras have also been reported in human and mouse cells [109,110,111,112,113,114,115,116,117], which are repeatedly detected and well-studied but in our opinion are technical artifacts [4]. They are frequently detected partly because in human and mouse cells the 16S rRNA is encoded by the mitochondrial genome that not only has hundreds or even thousands of copies in a single cell but also contains many reversely complementary regions [4].…”
Section: Rt or Pcr Creates Many Artifacts That Fabricate “Trans-spmentioning
confidence: 99%